Pleural empyema caused by lung hamartoma - Religioni, Jarosław; Orłowski, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
We present a case of a 59-year-old patient with a tumor of the left lung and concomitant empyema. Ultimately, we established that the cause of the disease was a giant hamartoma, which had been left untreated for years and had infiltrated the pleural cavity. The surgery enabled a positive final outcome to be achieved.